The doll-master eaudiobook And other tales of terror. - Oates, Joyce Carol (Tantor Media, 2019)
From one of our most important contemporary writers, The Doll-Master and Other Tales of Terror is a bold, haunting collection of six stories. In the title story, a young boy becomes obsessed with his cousin's doll after she tragically passes away from leukemia. As he grows older, he begins to collect "found dolls" from the surrounding neighborhoods and stores his treasures in the abandoned carriage house on his family's estate. But just what kind of dolls are they? In Gun Accident , a teenage girl is thrilled when her favorite teacher asks her to house-sit, even on short notice. But when an intruder forces his way into the house while the girl is there, the fate of more than one life is changed forever. In Equatorial , set in the exotic Galápagos, an affluent American wife experiences disorienting assaults on her sense of who her charismatic husband really is, and what his plans may be for her. In The Doll-Master and Other Tales of Terror , Joyce Carol Oates evokes the "fascination of the abomination" that is at the core of the most profound, the most unsettling, and the most memorable of dark mystery fiction.